A Comparative Study of Phenylephrine Hydrochloride and Ephedrine Hydrochloride for Treating Post-Spinal Hypotension in Lower Abdominal Surgeries - Manesh Naik, Deshavath; Mohanram, Aswin; Mita, Tellapati Kavya; Sekhar.T, Chandra (Journal of Neonatal Surgery, 2025)
Background: Post-spinal hypotension is a common complication during lower abdominal surgeries under spinal anesthesia. This study compares the efficacy of phenylephrine hydrochloride and ephedrine hydrochloride in treating post-spinal hypotension. Methods: Eighty patients aged 25–45 years with ASA physical status I or II, scheduled for elective lower abdominal surgeries under spinal anesthesia, were randomized into two groups. Group P received 100 µg intravenous phenylephrine, and Group E received 6 mg intravenous ephedrine upon a 30% drop in systolic blood pressure (SBP) from baseline. Hemodynamic parameters were recorded at specific intervals intraoperatively and postoperatively. Results: Phenylephrine restored SBP more rapidly than ephedrine (p<0.001). However, phenylephrine was associated with significant bradycardia compared to ephedrine (p<0.001). Side effects such as headache and bradycardia were more prevalent in the phenylephrine group, whereas nausea and vomiting were more common in the ephedrine group. Conclusion: Both phenylephrine and ephedrine are effective in managing post-spinal hypotension. Phenylephrine restores blood pressure more rapidly but has a higher incidence of bradycardia. Ephedrine maintains heart rate better but is less effective in rapidly increasing blood pressure.